Ein Käfig voller Narren nach dem Bühnenstück "Männer sind doch die besseren Frauen" von Jean Poiret - Molinaro, Edouard; Nannuzzi, Armando; Serrault, Michel; Tognazzi, Ugo; Maurier, Claire (MGM, 2009)
"La Cage aux Folles" are "birds of a feather," which are precisely and hilariously what do not flock together in this wonderful comedy from France. It's about the gay owner of a scandalous nightclub in St. Tropez, his transvestite lover, and how the owner reacts after his son returns home one day and announces he's going to marry a girl! ... Describing a comedy is always a risky business; the bare plot outline is, of course, no hint as to how funny a film is, and to steal the jokes is a misdemeanor. What I can say, though, is that "La Cage aux Folles" gets the audience on its side with immediate ease; it never betrays our confidence; it astonishes us with the inspiration and logic it brings to ringing changes on the basic situation. [rogerebert.suntimes.com]
Keywords: DVD-Video